(untitled) - Chang, Raymond (Boston, 2008)
Introduction, Atoms, molecules, and ions, Stoichiometry, Reactions in aqueous solutions, Gases, Energy relationships in chemical reaction, The electronic structure of atoms, The periodic table, Chemical bonding I : the covalent bond, Chemical bonding II : molecular geometry and hybridization of atomic orbitals, ...
Hóa học đại cương 1,Hóa học đại cương 2
Keywords: Chemistry,Lý thuyết hóa học; Textbooks,Sách giáo khoa